Improving Compressor Cooling System Temperature Control - Sharipov Farkhodjon Fazlitdinovich; Omonbaev Rakhmonjon Ravshan Ogli (Peerian Journals Publishing, 2024)
In the article, the achieved efficiency in automating the operation of compressor devices is based on reducing the human factor, safety, operational reliability, the ability to foresee accidents and reliable operation of hydraulic turbine devices
Keywords: Power station; hydroelectric power station; renewable energy sources